RADT-30. MULTISESSION RADIOSURGERY ALONE FOR TREATMENT OF PRESUMED MENINGIOMAS: AN INTERIM REPORT FROM A SINGLE INSTITUTION PROTOCOL. (12th November 2021) - Carrasquilla, Michael; Tai, Alexander; Forsthoefel, Matthew; Wang, Edina; Lei, Siyuan; Campbell, Lloyd; Suy, Simeng; Harris, Breant; Azumi, Norio; Berkowitz, Frank; Voyadzis, Jean-Marc; Kalhorn, Christopher; et al.
Abstract: PURPOSE: Meningiomas are the most commonly diagnosed primary intracranial tumor. Resection and single-fraction radiosurgery are treatment options with well-established long-term outcomes data. Multisession radiosurgery is an alternative treatment option with promising early results. However, mature outcomes literature does not yet exist. In this study, we report our institution's interim results on the efficacy and safety of 5-fraction radiosurgery alone for radiographically diagnosed meningiomas. MATERIALS AND METHODS: Between 2005-2015 all patients who completed treatment on a single institution protocol utilizing 5-fraction robotic radiosurgery alone for the treatment of progressing radiographically diagnosed meningiomas were eligible for inclusion. Local control was calculated using the Kaplan-Meier Method. RESULTS: Forty-four consecutive predominately female patients (84%) ranging in age from 33-85 (median: 59) were included in the present study. Median tumor volume was 4.05mm 3 (range: 0.94-15.4mm 3 ) and the majority of tumors were located at the base of skull (66%). A median dose of 25Gy (range: 25Gy-35Gy), was delivered to a median isodose line of 82%, (range: 70%-90%) over a median of 7 days (range: 5-11 days). Acute toxicity was minimal with 7 patients (15%) requiring a short course of steroids for symptomatic edema during treatment. Of 16 patients who presented with a cranial nerve deficit, symptom improvement was noted in 11 patients (69%). No permanent treatment related toxicity was noted in our cohort. The median radiographic follow-up was 6.9 years (range: 0.5-14.8 years). The 5 and 8-year local control rates were 100% and 95%. The median time to local failure (n=2) in our cohort was 8.2 years. CONCLUSIONS: The treatment of radiographically diagnosed meningiomas with 5-fraction robotic radiosurgery provides excellent local control to date, with low rates of acute and late toxicity. However, with late failures noted in our series, continued follow-up is needed to determine the optimal dose required for long-term tumor control.